The Effect of Plating, Ingredients, and Cooking Processes on the Acceptance and Authenticity of Ethnic Rice Dishes - Cho-Long Lee; Soo-Hyun Lee; Ga-Gyeong Seo; Jae-Hee Hong (Foods, 2020)
Familiarity and ethnic authenticity have a significant influence on the liking of ethnic food. Thus, it is crucial to identify the degree to which a dish can be modified in order to increase hedonic responses and familiarity without the loss of ethnic authenticity. This study determined the degree to which perceptions of the Korean rice dish, bibimbap, would vary upon modification of its ingredients, cooking process, or plating using the Southeast Asian market as a model system. The dish was prepared in Korean style or as Nasi Goreng, the Southeast Asian style. Eight formulations (2 ingredients × 2 cooking methods × 2 plating styles) were tested by panels, including 77 Southeast Asians and 72 Koreans. Hedonic responses, familiarity, ethnic authenticity, and purchase intent were evaluated using a nested analysis of variance. Ingredients and cooking methods had a significant influence on liking and perceived ethnic authenticity. In addition, plating had a substantial effect on the perception of ethnic authenticity and expected liking. Overall, the rate of positive responses increased when region-specific cooking processes and plating were matched. Taken together, our results suggest that modification of familiar dishes needs to be carefully considered as it can have complex effects on liking and perceived ethnic authenticity.